2018
DOI: 10.15252/embj.201797980
|View full text |Cite
|
Sign up to set email alerts
|

Continuous signaling of CD 79b and CD 19 is required for the fitness of Burkitt lymphoma B cells

Abstract: Expression of the B‐cell antigen receptor (BCR) is essential not only for the development but also for the maintenance of mature B cells. Similarly, many B‐cell lymphomas, including Burkitt lymphoma (BL), require continuous BCR signaling for their tumor growth. This growth is driven by immunoreceptor tyrosine‐based activation motif (ITAM) and PI3 kinase (PI3K) signaling. Here, we employ CRISPR/Cas9 to delete BCR and B‐cell co‐receptor genes in the human BL cell line Ramos. We find that Ramos B cells require th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 58 publications
3
65
0
Order By: Relevance
“…Ph-like and Ph + ALL cells also had very high levels of CD79A and CD79B proteins, which were comparable to levels detected in pre-BCR + KOPN-8 and SUP-B15 ALL cell lines ( Figure 5B). Prior studies have reported CD79A-and CD79B-induced phosphorylation of downstream pre-BCR molecules, such as BTK and ERK, in the absence of BCR stimulation or the BCR itself (44)(45)(46)(47). We thus assessed additional downstream pre-BCR signaling molecules and indeed identified that AKT, BTK, and ERK were highly phosphorylated in Ph-like ALL PDX cells ( Figure 5C).…”
Section: Resultsmentioning
confidence: 67%
“…Ph-like and Ph + ALL cells also had very high levels of CD79A and CD79B proteins, which were comparable to levels detected in pre-BCR + KOPN-8 and SUP-B15 ALL cell lines ( Figure 5B). Prior studies have reported CD79A-and CD79B-induced phosphorylation of downstream pre-BCR molecules, such as BTK and ERK, in the absence of BCR stimulation or the BCR itself (44)(45)(46)(47). We thus assessed additional downstream pre-BCR signaling molecules and indeed identified that AKT, BTK, and ERK were highly phosphorylated in Ph-like ALL PDX cells ( Figure 5C).…”
Section: Resultsmentioning
confidence: 67%
“…Lorric Delage, 1 Delphine Manzoni, 2 Charles Quinquenet, 3 Juliette Fontaine, 4 Alizée Maarek, 4 Kaddour Chabane, 2 Isabelle Mosnier, 2 Sandrine Hayette, 2 Evelyne Callet-Bauchu, 1,2 Beatrice Grange, 1,2 Correspondence: PIERRE SUJOBERT -pierre.sujobert@chu-lyon.fr doi: 10.3324/haematol.2018.203521…”
Section: Case Reportsmentioning
confidence: 99%
“…1 This transmembrane glycoprotein is an essential co-receptor of the B-cell receptor (BCR), 2 although it can also be activated in a BCR-independent manner. 3 The deleterious consequences of CD19 inactivation on B-cell development, described both in murine models and in human diseases, 4,5 are explained by the potential of CD19 to activate pro-survival pathways transduced by phosphatidylinositol-3-kinase (PI3K) or kinases from the Src family. Accordingly, the expression of CD19 is highly conserved in B-cell neoplasms, except in those derived from terminally differentiated cells such as plasmablastic lymphoma and multiple myeloma.…”
mentioning
confidence: 99%
“…Conversely, activation of GSK3β in MYC‐expressing lymphomas, achieved through PI3K inhibitors, was recently proposed as a strategy to overcome resistance of tumor B cells to BET inhibitors . A possible mediator of the signals delivered from the BCR to sustain lymphoma cell fitness is the BCR co‐receptor CD19, which facilitates the recruitment and subsequent activation of the PI3K/AKT complex . The negative regulation imposed by the BCR on GSK3β activity to ensure optimal growth of MYC lymphoma cells, strikingly resembles the contribution of the BCR in licensing the proliferation of wild‐type mature B cells in response to stimulation with TLR ligands .…”
Section: The Role Of the Bcr In Tumor B‐cell Fitnessmentioning
confidence: 99%